Analysis of the Systematic Relationships among Social Determinants of Health (SDH) and Identification of Their Prioritization in Iran Using DEMATEL Technique. - Mohammadkarim Bahadori; Ramin Ravangard (Tehran University of Medical Sciences, 2013)
Social determinants, similar to equity, have been considered by policymakers in many countries. However, there is not a correct and complete understanding of them. This study aimed to analyze the systematic relationships among social determinants of health (SDH) and identify their prioritization in Iran.This cross-sectional descriptive-analytical study was conducted in 2012. The target population consisted of 30 experts on SDH. Required data was collected using a questionnaire, as well as, nominal group technique (NGT). Then collected data were analyzed using MATLAB 7.9.0 and SPSS 18.0.Determinants of early life (EL), social gradient (SG), unemployment (U), stress (S) and addiction (A) were certainly affecting determinants on the system, which were placed in the cause group and ranked as the first to fifth priorities, respectively. While social exclusion (SE), food (F), social support (SS), work (W) and transport (T) were partially affected determinants and were placed in the effect group and ranked as the sixth to tenth priorities, respectively. Early life and transport were identified as the most affecting and affected determinants with the coordinates (2.16 and 0.75) and (1.68 and -0.47) on the SDH diagram, respectively.Improving the social and economic status, considering the early life, increasing the quality of education, and reducing unemployment and stress have effects on the other social determinants of health and provide opportunities for increasing equity.